Odonata (libélulas) do município de Luís Antônio, São Paulo, Brasil: relação com o uso do solo e riqueza faunística - Peruquetti, Patrícia Santos Ferreira (Universidade Federal de São Carlos, 2004)
Odonates are generalist predators both as aquatic larvae as aerial adults. They are found in all types of freshwater habitats and even in brackish waters in temperate and tropical climates. The larval is the longest stage in their life cycles and so more prone to be affected by anthropic effects on the aquatic systems and odonates have been used as indicator species water quality. A survey of the species occurring in the Luís Antônio Municipality, including the Jataí Ecological Station (EEJ) and the adjoining area (sugarcane monoculture) allowed to relate the distribution of odonate species to the land use. Ninety-nine species were collected, of which one species of Dicteriadidae; 2 of Calopterygidae, Corduliidae and Lestidae; 4 of Protoneuridae; 6 of Aeshnidae; 7 of Gomphidae; 23 of Coenagrionidae and 52 of Libellulidae. The monoculture area presented a larger species richness (lentic systems, 37±1 CI95%; lotic systems, 42±1 CI95%) than the EEJ (lentic systems, 34±1 CI95%; lotic systems, 13±1 CI95%). There were no significant differences between the physical and chemical variables of the two areas (for the lotic systems, t=1,16, p>0,05, gl= 8; for the lentic, t=0,58, p>0,05, gl= 4). The faunal similarity between the protected and the monoculture areas was low (CmH=0,473). In the clustering dendrogram 3 groups are formed: (1) EEJ streams; (2) streams and dams in sugarcane areas and (3) EEJ ponds/lakes. The larger species richness found in monoculture areas is probably a response to the impact caused by this land use, which creates new habitats that seemingly favor many odonate species. If "pest species" are invading natural areas, especially in lotic habitats, the most affected by anthropic alterations, their occurrence indicates these areas degradation and a lowering of their biotic integrity. The larger difference in species richness in lotic systems in EEJ and monoculture areas and the clustering of lotic and lentic habitats in the latter show that species typical of lentic habitats are invading lotic ones. The comparison of data from similar habitats but more preserved, as those of EEJ, can provide clues to evaluate the effects of environmental alterations caused by the monoculture. Sampling in degraded environments may lead to a wrong use of indicator species for environment quality.
Keywords: Odonata; Riqueza em espécies; Mata ciliar; Insetos aquáticos; Ecologia de comunidades; CIENCIAS BIOLOGICAS::ECOLOGIA